Diversity and Vertical Distribution of Epiphytic Angiosperms, in Natural and Disturbed Forest on the Northern Coast of Jalisco, Mexico - Flores-Argüelles, Alejandra; Espejo-Serna, Adolfo; López-Ferrari, Ana Rosa; Krömer, Thorsten (Frontiers in Forests and Global Change, 2022)
Background and Aims Epiphytes are an important component of tropical forests, also they are sensitive to disturbance and deforestation caused by humans, since they depend on their host trees and the micro environmental conditions that these provide. The aim of this study was to analyze the differences in species richness, composition, and vertical distribution of epiphytic angiosperms between areas with natural and disturbed forest at the Northern Coast of Jalisco state, Mexico. Methods The presence/absence of epiphytic angiosperms was evaluated in each vertical zone of a selected tree, as well as those present in the understory, both in natural and disturbed sites in three types of vegetation (gallery forest, oak forest, tropical semideciduous forest) with a total of 30 plots of 20 m × 20 m in six sites. Alpha diversity was calculated for each site, as well as species turnover (beta diversity) between habitats. An analysis of variance was performed to determine if there was a significant difference in species richness between sites and, also to compare the height and diameter at breast height (DBH) of the host trees. Multivariate analyzes were used to group the sites according to their floristic composition. Furthermore, a linear regression was performed to detect any relationship between the number of species and the phorophyte structure. Results We recorded 45 species, 29 genera and nine families of epiphytic angiosperms. The most diverse families were Bromeliaceae and Orchidaceae and the richest genus was Tillandsia. Although the disturbed sites had more species, a significant difference in richness was not found, except for the disturbed gallery forest. Epiphytic angiosperms presented a high beta diversity, since the sites shared only between 2 and 18% of the recorded species. The inner portion of the canopy (Z3 and Z4) hosted most of the species in all sites and the understory had a high representation of epiphytes except for the disturbed oak forest, where these were absent. A relationship between the DBH and the number of species was found only at the disturbed sites, however, it was highly influenced by the high number of taxa registered in disturbed gallery forest. Therefore, the size of the trees could not be considered a factor in determining the diversity of epiphyte species. Conclusion The diversity of epiphytic angiosperm species from the North Coast of Jalisco has not been severely affected by the human disturbance. Most of the species have morphological and physiological adaptations that allow their establishment and survival in adverse climatic conditions. Our results suggest that epiphytic angiosperms cannot be considered as a good indicator for natural or disturbed environments in this region but should be considered in environmental conservation, as they present a high beta diversity.